2002
DOI: 10.1097/00008571-200204000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2C9 polymorphisms: a comprehensive review of the in-vitro and human data

Abstract: The discovery of six distinct polymorphisms in the genetic sequence encoding for the cytochrome P450 2C9 (CYP2C9) protein has stimulated numerous investigations in an attempt to characterize their population distribution and metabolic activity. Since the CYP2C9*1, *2 and *3 alleles were discovered first, they have undergone more thorough investigation than the recently identified *4, *5 and *6 alleles. Population distribution data suggest that the variant *2 and *3 alleles are present in approximately 35% of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
462
4
14

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 616 publications
(506 citation statements)
references
References 70 publications
22
462
4
14
Order By: Relevance
“…Finally, CYP2C9*6 variant allele has been identified; this is a new null polymorphism containing an adenine base pair deletion at nucleotide 818, which results in a premature stop codon and a truncated inactive protein. 8,9 The genotypic features of the CYP2C9 gene have been studied in several ethnic groups (Table 1); very low frequency of alleles CYP2C9*2 and *3 has been found among Oriental populations. We have previously shown the genetic polymorphism of CYP2C9 among Spaniards.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, CYP2C9*6 variant allele has been identified; this is a new null polymorphism containing an adenine base pair deletion at nucleotide 818, which results in a premature stop codon and a truncated inactive protein. 8,9 The genotypic features of the CYP2C9 gene have been studied in several ethnic groups (Table 1); very low frequency of alleles CYP2C9*2 and *3 has been found among Oriental populations. We have previously shown the genetic polymorphism of CYP2C9 among Spaniards.…”
Section: Introductionmentioning
confidence: 99%
“…Population differences in CYP2C9 activity and allelic frequencies of CYP2C9 variants There are substantial differences in the allelic frequencies of CYP2C9 variants, at least for CYP2C9*2 and CYP2C9*3 alleles, across different ethnic populations: the respective allelic frequencies of CYP2C9*2 and CYP2C9*3 in African-Americans (1-3.6% and 0.5-1.5%, respectively) and Asians (0% and 1.7-5%, respectively) tended to be lower than the corresponding values of Caucasians (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).1% and 5.3-10%, respectively). 8,9 As the enzyme activities of CYP2C9 variant proteins are reduced as compared with the wild-type protein 42 at least in in vitro experiments, there is a possibility that the population differences in the allelic frequencies of distinct CYP2C9 variants may emerge as those in certain phenotypic traits of CYP2C9 (eg, CL po,u ).…”
Section: Effects Of Cyp2c9 Genotypes On (S)-warfarin Metabolismmentioning
confidence: 98%
“…8,9 As the enzyme activities of CYP2C9 variant proteins are reduced as compared with the wild-type protein 42 at least in in vitro experiments, there is a possibility that the population differences in the allelic frequencies of distinct CYP2C9 variants may emerge as those in certain phenotypic traits of CYP2C9 (eg, CL po,u ). We have recently studied the population differences of hepatic CYP2C9 activity using CL po,u for (S)-warfarin as a specific in vivo probe for the CYP isoform between Caucasians and Japanese patients and found that the population mean for body weightnormalized CL po,u for (S)-warfarin obtained from Japanese patients was significantly greater than that for Caucasian patients.…”
Section: Effects Of Cyp2c9 Genotypes On (S)-warfarin Metabolismmentioning
confidence: 99%
See 2 more Smart Citations